Zaznavanje kakovosti zraka v Ljubljani - Vintar Mally, Katja (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2016)
This article presents the results of research examining perceptions of air quality in the city of Ljubljana based on extensive interviews. Perceptions of air quality are also compared with perceptions of other environmental problems, as well as to data from air quality monitoring in the study area. The findings suggest that residents perceive air pollution as a major environmental problem in the city and that people remain firmly convinced of Ljubljana%s poor air quality despite its overall improvement.
Keywords: environmental protection; geografija; geography; Ljubljana; onesnaženost; onesnaževanje okolja; pollution; varstvo okolja; zrak